Cambridge IGCSE chemistry coursebook - "Harwood, Richard" (Cambridge University Press London, 2014)
This edition of our successful series to support the Cambridge IGCSE Chemistry syllabus (0620) is fully updated for the revised syllabus from first examination from 2016.